Case Report: Extraocular muscles paralysis associated with GAD65 antibody: a case series study - Zhang, Heyu; Yue, Jiajia; Lian, Chun; Long, Youming; He, Dan (Frontiers in Immunology, 2023)
To explore the clinical manifestations of glutamic acid decarboxylase 65 (GAD65) antibody-positive patients with extraocular symptoms and the possible mechanism.Assays for the presence of GAD65 antibodies were performed on patients' serum and cerebral spinal fluid (CSF). The brain and ocular structures involved in eye movement were assessed via magnetic resonance imaging (MRI). Tests such as electromyography (EMG), particularly repetitive nerve stimulation (RNS), and neostigmine tests were utilized for differential diagnosis. Additionally, the interaction of GAD65 antibodies with muscle tissue was confirmed using immunofluorescence techniques.Each patient exhibited symptoms akin to extraocular myasthenia gravis (MG), with two individuals reporting diplopia and two experiencing ptosis. GAD65 antibodies were detected in either the serum or CSF, which were shown to bind with monkey cerebellum slides and mouse muscle slides. Neuroimaging of the brain and extraocular muscles via MRI showed no abnormalities, and all patients tested negative for the neostigmine test, RNS via EMG, and the presence of MG antibodies. However, thyroid-related antibodies were found to be abnormal in four of the patients.Our results showed that GAD65 antibodies are not only associated with encephalitis, cerebellum ataxia or stiff-person syndrome caused by the decrease of GABAergic transmission but also diplopia and blepharoptosis. Therefore, we should pay more attention to extraocular muscle paralysis patients without pathogenic antibodies directed against the components of neuromuscular junctions.